2012
DOI: 10.2500/aap.2011.32.3518
|View full text |Cite
|
Sign up to set email alerts
|

Asthma management and control in the United States: Results of the 2009 Asthma Insight and Management survey

Abstract: Past asthma surveys have shown suboptimal management and control of asthma in the United States. No major survey of asthma management has been conducted since the Third Expert Panel Report for the National Asthma Education and Prevention Program (NAEPP) guidelines on diagnosis and treatment of asthma (August 2007). This study was designed to report asthma management and control results from the Asthma Insight and Management survey of U.S. patients and physicians. A telephone-based survey was conducted during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
99
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(115 citation statements)
references
References 0 publications
10
99
1
5
Order By: Relevance
“…In addition, we also were struck by the findings that only a small subset of these patients received optimal long-term control treatment and outpatient management by asthma specialists, both of which are recommended by the 2007 National Institutes of Health guidelines. 6 Parallel to our findings, results of studies reported underuse of long-term control medications, asthma education, and outpatient care by specialists [16][17][18][19][20] as well as suboptimal coordination of care between EDs and asthma centers. 21 Analysis of these data collectively indicates that quality improvement efforts in longitudinal (chronic asthma) management should be the priority areas of guideline dissemination and adoption initiatives.…”
Section: Ongoing Large Burden Of Frequent Ed Users For Acute Asthmasupporting
confidence: 87%
“…In addition, we also were struck by the findings that only a small subset of these patients received optimal long-term control treatment and outpatient management by asthma specialists, both of which are recommended by the 2007 National Institutes of Health guidelines. 6 Parallel to our findings, results of studies reported underuse of long-term control medications, asthma education, and outpatient care by specialists [16][17][18][19][20] as well as suboptimal coordination of care between EDs and asthma centers. 21 Analysis of these data collectively indicates that quality improvement efforts in longitudinal (chronic asthma) management should be the priority areas of guideline dissemination and adoption initiatives.…”
Section: Ongoing Large Burden Of Frequent Ed Users For Acute Asthmasupporting
confidence: 87%
“…By utilising a comprehensive structured asthma review approach, the results of this study helped to identify populations that should be targeted by tailored interventions to improve practice. Moreover, this approach provided valuable insight into patient behaviour regarding inhaler technique which would have been impossible to obtain through other approaches such as online surveys utilised in other studies [13][14][15][16][17][18][19][20]24,25,27]. While many multinational studies have shown that poor asthma control remains prevalent, few studies have assessed asthma control in real-life clinical practice and none in the Australian population, a population with one of the highest asthma prevalence rates in the world (in 2015, there were 2.4 million Australians with a recorded diagnosis of asthma, i.e., 9.9% of the population) [2].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, a number of multinational surveys have shown that asthma control, when measured by various instruments, remains sub-optimal [13][14][15][16][17][18][19][20]. Several international 'real-life' clinical studies conducted in general practice and hospital outpatient clinics have also shown that poor asthma control is prevalent, despite the availability of treatments [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Europe and Canada, 81% (n = 2003) of surveyed patients perceived their asthma as completely or well controlled but, according to the Global Initiative for Asthma (GINA) guidelines, only 18% of these patients would have been classified as having controlled asthma. This trend extends globally in Latin America [26], Asia-Pacific [24], US [27] and the UK [28].…”
Section: Introductionmentioning
confidence: 99%
“…For example, patients tend to believe their asthma is under control even when they have experienced frequent symptoms, have used their reliever inhaler regularly or have had an acute exacerbation within the last year [21][22][23]. A series of multinational surveys [24][25][26][27] to gain insights on the attitudes and perceptions of patients with asthma found that patients' perceptions of how efficiently they were controlling their asthma were inconsistent with objective criteria recognised by asthma control guidelines. For example, in Europe and Canada, 81% (n = 2003) of surveyed patients perceived their asthma as completely or well controlled but, according to the Global Initiative for Asthma (GINA) guidelines, only 18% of these patients would have been classified as having controlled asthma.…”
Section: Introductionmentioning
confidence: 99%